ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT (Studi Empiris Pada Auditor KAP Di Jawa Tengah) - Vita Verdiana Sari, 11.05.52.0073; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
This research intend to test the effect of experience, independence, due professional care, accountability, ethics audit, competence to audit quality.Â Population in this research is auditor which is work at Kantor Akuntan Publik (KAP) at Central Java. The sampels pick up do with method purposive sampling and there is 63 responded in total. Thr primary data pick up methot which is use is questioner method. And data analysis use multiple linear regression model.Â The research result shows that experience, independence, due professional care, accountability, ethics audit, competence have a really good effect to audit quality.Keywords: Experience, Independence, Due Professional Care, Accountability, Ethics Audit, Competence, Audit Quality